Exploring the link between integrated leadership-in-government and follower happiness: the case of Dubai. (December 2019) - Mathias, Megan; Fargher, Scott; Beynon, Malcolm
This study develops a concept of integrated leadership-in-government as a global and multifaceted construct for the first time in the Dubai and wider Gulf context. Leadership-in-government combines eight public leadership roles articulated in recent literature, as performed by managers at all levels within the government hierarchy. The eight public leadership roles are: accountability, rule-following, political loyalty, network governance, task-oriented, relations-oriented, change-oriented and diversity-oriented leadership. Data is gathered via a survey of over 900 employees in Dubai government organisations. Findings from the empirical analysis suggest that a manager's performance of integrated leadership-in-government has a significant effect on employee happiness, as measured through job satisfaction and self-perceived performance. Points for practitioners: Leadership in government involves an integrated set of roles specific to the context of government – making it different to leadership in other contexts. As perceived by employees, leadership within government organisations in Dubai is, however, similar to leadership within government organisations in Western democracies. Employees report that leadership in government has a positive effect on their happiness, in terms of their job satisfaction and self-perceived performance.